The Anesthesiology trainee’s perspective on the impact of COVID-19 pandemic on residency - Vieira, Inês Regina Ferreira (Journal of the Portuguese Society of Anesthesiology, 2021)
Introduction: The Portuguese Trainee Network section of the Portuguese Society of Anesthesiology joined the group for the study of the psychological impact of COVID, from the Valença General and Academic Hospital, to understand the impact of the COVID-19 pandemic on the Anesthesiology trainees in Portugal. Methods: From October to December of 2020, the answers to the Portuguese translated version of the questionnaire were collected online. Results: From the 158 answers obtained, the main results were: 74.7% of trainees had their rotations interrupted, 69% referred that the acquired knowledge during that period did not compensate the expected learning from the previously scheduled rotations, 74.7% mentioned an increase in their responsibility and autonomy, 45.6% felt loneliness and 4.4% needed psychological support. Discussion: Most trainees did not maintain the same area of work and were redirected according to need and year of residency. Similarly to other health professionals, trainees reported an increase in the number of working hours during the pandemic months. Alongside, there was also an increase in their responsibility and autonomy. Conclusion: Anesthesiology trainees are a vulnerable population, and their mentoring is essential to assure the fulfillment of residency programs. The acquisition of essential technical and non-technical skills should be guaranteed, as should their physical and mental well-being.